(untitled) (Research, Society and Development, 2022)
SARS-CoV-2 infection has important impacts on the provision of health services in general. To analyze the published research on this impact on pediatric palliative care (PPC). This study is an integrative literature review, carried out at the "Biblioteca Virtual de Saúde" (BVS) in February 2022. After reading 9 articles, it was found that the main impacts on the PPC during the pandemic were the reduction in the quality of health care, damage to mental health, economic insecurity and unemployment of professionals. The use of telecommunications and personal protective equipment and social distancing made it difficult the connection between the professional, the patient and the family, affecting the quality of care. Given the numerous challenges experienced in the execution of palliative care during this health crisis, it is clear the need to implement an action plan for the improvement and strengthening of PPCs. Likewise, the need for more studies to assist in the creation of more assertive actions at pediatric palliative care in this pandemic reality is reinforced.